Is the study of memory unduly preoccupied with its sins?. Issue 1 (2nd January 2022) - Baddeley, Alan D.
ABSTRACT: A broad functional approach is taken to the analysis of human memory. The overall importance of episodic memory, the capacity to remember specific events, is illustrated by the devastating effect that loss of this aspect of memory has on the capacity to cope in the case of densely amnesic patients. Recent applied research has however focussed heavily on factors compromising the reliability of eyewitness testimony in the forensic field and on the creation of false memories. While acknowledging the progress made on this issue, it presents two dangers. The first is practical, the danger of generalising too readily from laboratory-influenced simulations that differ in important ways from the context to which they are applied. This suggests a need for fewer but more realistically representative studies. The second is a broad theoretical issue, that of extending the findings from this important but limited applied area, within which precise detail may be crucial, to the whole of memory, consequently failing to appreciate its many strengths.